The Use of Facebook and Development of Students’ Writing Skills - Ni Made Anggi Arlina Putri (IJET (Indonesian Journal of English Teaching), 2018)
This qualitative study investigates the extent to which Facebook supports EFL teaching and learning, potential and challenges of using Facebook on English writing subject, and teacher and students’ responses toward Facebook implementation. Conducted at a junior high school in Surakarta, this study involved one EFL teacher and five students as participants. Data from classroom observation, interview, and documentation suggest that the use of Facebook as a technology-based media in English writing classroom enhances the discussion and participation in teaching-learning activities. After a class discussion on Facebook facilitated by the teacher has allowed the student to visit the Facebook and to have a group discussion. The social media has provided students with a better learning process through a variety of multi-media resources which enhance autonomous learning strategies and improves their achievement of English writing.